PELATIHAN TEKNIK PUBLIC SPEAKING BAGI GURU DALAM PENGAJARAN BAHASA INGGRIS DI PONDOK PESANTREN DI KABUPATEN KARAWANG - Bani Ahmad, Yousef; Mobit; Andriamella Elfarissyah; Hasna Afifah; Dinda Annisa Syahida; Diajeng Nada Vici (Nusantara Hasana Journal, 2022)
This training is a continuation of research activities that focus on the Public Speaking Ability of Teachers in Teaching English at Islamic Boarding Schools in Karawang Regency. The problems that exist today are the need for self-development for teachers in Islamic boarding schools in Karawang district, the strong desire of teachers to improve teaching skills inside and outside the classroom, the need to master public speaking skills that can convey messages effectively and persuasive, it has never been studied specifically about the technique of public speaking as one of the keys to success in conveying material in an easy and fun way, teachers still need to be assisted in making the structure of delivering messages starting from the opening, delivery of material and also closing using English. After participating in the training, the teachers were happy because they knew and understood about public speaking techniques using English. The technique understood by the teachers is about the vocabulary that is often used in the opening, being able to understand the technique of conveying a message in a persuasive manner and closing it elegantly. The output target is to make a video about public speaking that will be uploaded to YouTube.